2021
DOI: 10.1038/s41598-021-04291-8
|View full text |Cite
|
Sign up to set email alerts
|

Biased TCR gene usage in citrullinated Tenascin C specific T-cells in rheumatoid arthritis

Abstract: We aimed to search for common features in the autoreactive T cell receptor (TCR) repertoire in patients with rheumatoid arthritis (RA), focusing on the newly identified candidate antigen citrullinated Tenascin C (cit-TNC). Mononuclear cells from peripheral blood or synovial fluid of eight RA-patients positive for the RA-associated HLA-DRB1*04:01 allele were in-vitro cultured with recently identified citrullinated peptides from Tenascin C. Antigen-specific T cells were isolated using peptide-HLA tetramer staini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…In support of the observed TRBV20-1 bias, we have recently demonstrated a skewing of this gene segment in antigen-specific T cells recognizing citrullinated tenascin-C in peripheral blood and synovial fluid from RA patients with established disease (39). Importantly, it has also previously been shown that variable gene usage is in part influenced by HLA type (40), which might also contribute to our findings.…”
Section: Discussionsupporting
confidence: 86%
“…In support of the observed TRBV20-1 bias, we have recently demonstrated a skewing of this gene segment in antigen-specific T cells recognizing citrullinated tenascin-C in peripheral blood and synovial fluid from RA patients with established disease (39). Importantly, it has also previously been shown that variable gene usage is in part influenced by HLA type (40), which might also contribute to our findings.…”
Section: Discussionsupporting
confidence: 86%
“…These novel findings therefore demonstrate that TCR gene usage in IGRP 206-214 –reactive CD8 T cells is even more restricted than previously thought. Evidence of restricted TCR gene usage in IGRP 206-214 –reactive CD8 T cells may also warrant the investigation of TCR gene usage in T cells reactive to other commonly targeted β cell epitopes, such as insulin ( Amdare et al, 2021 ), at the single-cell level; these data parallel findings of restricted TCR repertoires among autoreactive T cells found in other autoimmune disorders such as experimental autoimmune encephalomyelitis ( Acha-Orbea et al, 1988 ; Urban et al, 1988 ; Sakai et al, 1989 ), polymyositis ( Mantegazza et al, 1993 ), rheumatoid arthritis ( Williams et al, 1992 ; Sharma et al, 2021 ), thyroiditis ( Martin et al, 1999 ), and primary biliary cirrhosis ( Moebius et al, 1990 ). It would also be valuable to apply scTCR-seq to CD8 T cells targeting other autoantigens in the islets of NOD mice to see if this trend holds for CD8 T cells targeting other antigens; although we studied IGRP 206-214 –nonreactive CD8 T cells in bulk in this study, we did not separately sort and sequence CD8 T cells targeting specific autoantigens other than IGRP 206-214 because of technical limitations of cell recovery.…”
Section: Discussionmentioning
confidence: 84%
“…3 f). Using GLIPH2 (Sharma et al 2021 ), we used publicly available data from a cohort of JIA patients, as reported by Henderson et al (Henderson et al 2016 ), to check TCR level similarity between the two cohorts. All patterns found in the healthy samples and Lyme disease patients were removed to retain possible RA associated motifs only.…”
Section: Resultsmentioning
confidence: 99%